Rekomendasi Font atau Model Tulisan dalam Pembuatan Akta Notaris - Dewi, Ni Luh Pooja; Yusa, I Gede (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
The purpose of this research is to analyze the font settings or deed writing model. So far, the regulation for writing deeds in UUJN is not regulated. In order not to make a mistake in choosing a writing model, it is necessary to determine the types of font models of word writing characters in deeds. This research method uses normative legal research, by analyzing data descriptively. This normative research issue is the vacuum of norm of setting the font of the writing character model in the deed so that it can be constructed into a new norm so that the writing of the deed is more appropriate in choosing the writing model. The results of the study explained that it is true that UUJN does not regulate the use of fonts or writing models directly, but notaries in writing are hereby required to carefully choose based on their principles. The fonts recommended by the author are times new roman, calibri, book antiqua and each other but can also use other fonts with a note that they do not violate the principles of good and correct writing.